Analisis Strategi Komunikasi Pembelajaran Daring Siswa Sekolah Pelita II di Masa Covid-19 - Tiffany Gintara; Sinta Paramita; Doddy Salman (Kiwari, 2022)
As a result of the emergence of the Covid-19 virus that occurred, it had a fairly large impact throughout the world, one of which was Indonesia. The impact of Covid-19 can be felt in various sectors, including in the field of education. Inside, face-to-face learning is shifting to online learning which is one of the logical consequences of today's technological developments. This study aims to analyze the application of communication strategies to Pelita II Elementary School students in online learning during the Covid-19 period, using a qualitative case study method and the model of analysis to see the various problems that are often encountered in Pelita II elementary school during online learning that takes place through the time. Using the theory of diffusion of innovation in analyzing this research problem. The results of this study indicate that the implementation of online learning at SD Pelita II starts from the preparation of the teacher itself by teaching using a strategy that is to create the same understanding and thoughts as the basic form of communication. In addition, the communication process that occurs during online learning is conveyed through the communicator (teacher) to the communicant (student). Kemunculan virus Covid-19 yang terjadi, memberikan dampak yang cukup besar bagi seluruh dunia, salah satunya adalah negara Indonesia. Dampak Covid-19 dapat dirasakan di berbagai kalangan sektor, termasuk di bidang pendidikan. Maka dari itu, pembelajaran tatap muka bergeser ke pembelajaran daring yang merupakan salah satu konsekuensi logis dari perkembangan teknologi saat ini. Penelitian ini bertujuan untuk menganalisis penerapan strategi komunikasi pada siswa SD Pelita II dalam pembelajaran daring pada masa Covid-19, dengan menggunakan metode studi kasus kualitatif. Model Analisis untuk melihat berbagai permasalahan yang sering ditemui di SD Pelita II dalam pembelajaran daring yang berlangsung. Menggunakan teori difusi inovasi dalam menganalisis permasalahan penelitian ni. Hasil penelitian ini menunjukkan bahwa pelaksanaan pembelajaran daring di SD Pelita II dimulai dari persiapan guru itu sendiri dengan mengajar menggunakan strategi yaitu menciptakan pengertian dan pemikiran yang sama sebagai bentuk dasar komunikasi, proses komunikasi yang terjadi saat pembelajaran daring yaitu disampaikan melalui komunikator (guru) kepada komunikan (siswa).